E-Commerce Within 3D Environment - Khaw, Kien Weng (Universiti Sains Malaysia, 2005)
With the advent of cheap and fast computer, the notion of 3D graphics has been very popular lately, from video games to weather simulations to movies that give us a glimpse of virtual reality. The World Wide Web has gained even more popularity. Virtual Reality Modeling Language (VRML) was born to solve this problem: how to put compelling 3D onto every PC connected to the Web. One of the effective applications of 3D on the Web is 3D E-Commerce. Most of the E-Commerce web sites currently available on the internet are presenting their products to their customers using 2D images. Due to the limitations of text and 2D graphics, the customers can just have a vague picture of the product. They could not really know how the product looks like in reality. With 3D environment or virtual reality, the customer of the E-Commerce web site may rotate a product to have a 360-degree view of that product. Rather than a 2D image, the customer can choose how to look at the model or world, the viewer can navigate the world and the most interesting is the file size can often be much less. 3D E-commerce presents the most realistic and detailed view of products to customers. This project is to investigate the feasibility of E-Commerce within 3D environment. In this project, e-commerce within 3D environment is developed. A case study of a furniture shop is considered in this project. VRML is used to develop the 3D objects and environment in the project. In order to provide text and navigation aids to help the user read about and interact with the VRML world, the web site is developed by integrating the VRML world with Hypertext Markup Language (HTML) text. Just like any other typical e-commerce web site, a server side application and database supports is a must. In this project, Java Server Pages (JSP) is used to build the server side program which is responsible to generate the web pages with the combination of static and dynamic contents and to communicate with the database. Tomcat is used as the container for running the JSP web application. MySQL, a DBMS, is used to build and manage the database for the project.